THE URGENCY OF EVALUATION IN THE LEARNING OF ISLAMIC RELIGIOUS EDUCATION AT ANTAM POMALAA JUNIOR HIGH SCHOOL, KOLAKA DISTRICT - Sutrisna, Saleh (IJBLE Scientific Publications Community Inc., 2023)
This study examines the significance of evaluating Islamic Religious Education at Antam Pomalaa Junior High School in Kolaka Regency. The objectives of the study were to determine the significance of evaluation in the learning process of Islamic Religious Education at the school, the learning methods and assignment systems used in evaluating Islamic Religious Education at Antam Pomalaa Junior High School, and the types of tests used in evaluating the learning process of Islamic Religious Education at Antam Pomalaa Junior High School. This qualitative descriptive field study presents the researchers' findings regarding the significance of assessment in the Islamic Religious Education learning process at Antam Pomalaa Junior High School in Kolaka. This study concluded using qualitative data analysis methods, essentially data described in words or phrases divided into categories. A rare third is interactive and includes (a) data reduction, (b) data display, and (c) conclusion (verification). Based on the collected, described, and analysed data, the author can conclude that the evaluation of the Islamic Religious Education learning process at Antam Pomalaa Junior High School has not reached the desired stage due to a lack of qualified Islamic Religious Education teachers. This study's findings can inform the significance of assessment in the teaching and learning of Islamic religious education, particularly at Antam Pomalaa Junior High.